Cultivation and characterisation of the surface markers and carbohydrate profile of human corneal endothelial cells. (14th February 2017) - Nagymihály, Richárd; Veréb, Zoltán; Albert, Réka; Sidney, Laura; Dua, Harminder; Hopkinson, Andrew; Petrovski, Goran
Abstract: Background: The study aims to characterise human corneal endothelial cell (HCEnC) cultures generated by the peel‐and‐digest method based on their surface protein/carbohydrate expression pattern. Methods: Quantitative polymerase chain reaction was used to compare expression of vimentin, CD90, Cytokeratin‐19, ZO‐1 and Claudin 14 in cultured HCEnC and cell line B4G12 versus stromal cells. Fluorescence‐activated cell sorting was used to assess surface protein distribution of cultured and uncultured HCEnC. Distribution of surface proteins/carbohydrates was visualised by immunofluorescent and lectin staining. Results: Human corneal endothelial cell and B4G12 showed lower expression level for vimentin, CD90, Cytokeratin‐19 compared with stromal cells; while ZO‐1 was expressed in endothelial cells, Claudin 14 was detected in B4G12 only. Fluorescence‐activated cell sorting analyses revealed CD166, CD47, CD44, CD54, CD73, CD90, CD105, CD106, CD112, CD146 and CD325 to be present, with CD34 to be absent from cultured HCEnC. Freshly isolated, non‐cultivated HCEnCs were CD90, CD73, CD146 and CD325 positive. Carbohydrates were detected by lectins LCA, PHA E, PHA L, PSA, sWGA, Con A, RCA 120 and WGA, but cultured HCEnC showed negative for GSL I, SBA, DBA, PNA and UEA I. Conclusion: Cultures established by the peel‐and‐digest method are probably not prone to stromal contamination, but the cells are likely to undergo endothelial‐to mesenchymal transition as suggested by apparent morphological changes.